Cluster randomised controlled trial to determine the impact of an activity enabling uniform on primary school student's fitness and physical activity: study protocol for the Active WeAR Everyday (AWARE) study. Issue 9 (22nd September 2022) - Nathan, Nicole; McCarthy, Nicole; Hall, Alix; Shoesmith, Adam; Lane, Cassandra; Jackson, Rebecca; Sutherland, Rachel; Groombridge, Daniel; Reeves, Penny; Boyer, James; Duggan, Bernadette; Wolfenden, Luke
Introduction: Multicomponent school-based physical activity (PA) interventions can improve students' cardiorespiratory fitness (CRF) and PA. Due to the complex nature of such interventions when delivered at scale their effect sizes markedly reduce. Modifying student school uniforms, so that they are more PA enabling, may be a simple intervention that could enhance student health. The primary aim of this trial is to assess the effectiveness of an activity enabling uniform intervention (shorts, polo shirt and sports shoes) in improving children's CRF. Methods and analysis: A cluster randomised controlled trial will be conducted in 24 primary schools in New South Wales (NSW), Australia. Schools will be randomly allocated to either intervention or usual practice following baseline data collection. Active WeAR Everyday intervention schools will allow students in grades 4–6 (aged approx. 9–12 years) to wear their existing sports uniform (shorts, polo shirt and sports shoes) every day. To avoid any financial cost to students they will be provided with two additional sports shirts and one pair of shorts. Study outcomes will be assessed at baseline and 9 months postbaseline. The primary outcome is students' CRF measured using the 20 m multistage fitness test. Secondary outcomes include students': mean daily steps and steps/minute measured via accelerometer, quality of life, mental well-being and perceived PA self-efficacy. The acceptability, feasibility and cost of the intervention will be assessed. Analyses will be performed using an intention-to-treat framework. Linear mixed effects regression models will be used to assess intervention effects on the primary outcome at follow-up. Planned exploratory analyses will examine effects by subgroups (eg, gender). Ethics and dissemination: This study has received approval from Hunter New England Local Health District Human Ethics Committee (2020/ETHO2602) the University of Newcastle, Human Research Ethics Committee (H-2021-0013), NSW Department of Education (SERAP: 2020387) and Catholic School Offices. Trial registration number: ACTRN12621000201875.